O discurso sobre a improdutividade do trabalhador brasileiro em textos jornalísticos: análise dialógica - Feitosa, Erike Luiz Vieira (2016)
This study is a bakhtinian dialogic discourse analysis (DDA) whose initial object is the statements published in April 2014 by the british magazine The Economist about the alleged lack of productivity of Brazilian workers. Other three opinative brasilian texts, that coment the foreign reporting, composes the corpus of this research: two newspapers editorials, one of Folha de S. Paulo and the other of Gazeta do Povo, plus a magazine editorial, from Carta Capital. The study highlights the axiologic position of these publications, interpreting the assumptions and intentions present in his speeches, and identifying their main interlocutors. The research demonstrates dialogic tensions between spokespersons of capital and labor categories. In the discursive context analyzed, the second is subordinate to the first, in a situation of dispute - political, economic, and electoral - by the Brazilian state. Regarding the field of ideology, the dissertation highlights the clash between the neoliberal/classical economic prescriptions and the heterodox economic vision (keynesian), the latter associated with dos Trabalhadores (Worker’s Party) governments. The study shows that the DDA used as a method that enables certain reading opinionative nature of texts, especially the editorial genre, is an appropriate approach to understanding the discursive matrices that permeate other products and journalistic genres that, when considering certain aspects of material reality, end up interfering in it. Also points out that, contrary to what might be expected, the Brazilian publications are not countered the controversial thesis defended by The Economist, positioning itself in the interests of or assuming analytical omission posture. With a strongly monological tone, the texts analyzed consider worker productivity, fundamentally, from the point of view of capital accumulation. Thus, to label the Brazilian and their country of unproductive, suggests that both (country and worker) should produce more, thus benefiting the capital and disregarding subjective aspects related reifying it. In addition to technical and scientific data, taken as irrefutable by journalistic publications, structure this discursive construction a stereotype that is long lasting rescues the colonial image of a native little inclined to work, whose life would be dedicated to idleness, a lazy bloke, a foreign to the superiority of economicexpansionist eurocentric culture that overemphasizes work, production, constant generation of surplus wealth. Expounding on the social consequences of the current capitalist setup, the study points to the need to rescue the notion of otherness, not from a theoretical point of view, but also in field of the everyday ideology. Finally, emphasize that the rescue and the use of culturally stereotypical lazy brazilian (unproductive) interferes into the formation of a self-consciousness of the workers and the image that others (the world) have of them (us).